Alkaline phosphatase activity sensitive to environmental salinity and dopamine in muscle of the euryhaline crab Cyrtograpsus angulatus - Pinoni, Silvina Andrea (2004)
The occurrence, characteristics and response to environmental salinity and dopamine of alkaline phosphatase (AP) activity were studied in chela muscle of the euryhaline crab Cyrtograpsus angulatus from Mar Chiquita coastal lagoon (Buenos Aires Province, Argentina). Chela muscle exhibited a high AP activity with a Michaelis –Menten kinetic (Km=1.21 mM). AP activity was strongly inhibited by EDTA (I50=2.26 mM). AP activity appeared to be sensitive to environmental salinity. In crabs acclimated to low salinity (10x) AP activity was lower than in 35x salinity. Upon an abrupt change to reduced salinity a short-term decrease of AP activity occurred, concomitant with the transition to hyperregulation. Furthermore, AP activity appeared to be under hormonal control since it was inhibited ‘‘in vivo’’ by 10 4 M dopamine. The response to both environmental salinity and dopamine suggests that AP activity could be a component of muscle regulatory mechanisms at the biochemical level secondary to hyperregulation of C. angulatus. The possible functional relationship of AP activity with Na+ /K+ ATPase in muscle is discussed.